Baicalein-functionalized collagen scaffolds direct neuronal differentiation toward enhancing spinal cord injury repair. (13th December 2022) - Qian, Lin; Yang, Keni; Liu, Xiru; Zhang, Lulu; Zhao, Haitao; Qiu, Lin-Zi; Chu, Yun; Hao, Wangping; Zhuang, Yan; Chen, Yanyan; Dai, Jianwu
Abstract : Baicalein was discovered to direct neuronal differentiation. Based on this, a baicalein functionalized collagen scaffold (BFCS) was developed for spinal cord injury (SCI) repair, which enhanced neurogenesis and motor functional recovery of SCI rats. Abstract : Spinal cord injury (SCI) repair remains a major challenge in clinics. Though neural stem cells (NSCs) have shown great potentials in SCI treatment, their applications were hampered since they primarily differentiate into astrocytes rather than neurons in the injured area, indicating a high demand for effective strategies to direct neuronal differentiation. Baicalein is a clinical drug with multiple pharmacological activities, while its effects on NSCs have rarely been reported. In the current work, inspired by a similarity of the metabolic reprogramming required in neuronal differentiation and that involved in chemoresistance reversal of cancer cells induced by baicalein, we studied the role of baicalein in NSC differentiation and discovered its promotion effects on neuronal differentiation. Based on this observation, baicalein-functionalized collagen scaffolds (BFCSs) were developed and applied for SCI treatment. The BFCSs released the payload in a sustained way and possessed comparable physical properties to the commonly used collagen. Both in vitro studies with primary NSCs and in vivo studies in SCI rats showed that the BFCSs containing a low amount of baicalein can facilitate not only neurogenesis and axon extension, but also reduce astrocyte production and glial scar formation. More importantly, the BFCS implantation led to improvement in the motor functional recovery of SCI rats. Thus, the BFCSs provided a potential strategy to induce neuronal differentiation towards facilitating SCI repair, as well as for the treatment of other central nervous system injuries.